Aceh, Masalah Narkoba Dan Pelacuran Dalam Sorotan: Sebuah Tinjauan Awal - Fajri M Kasim (Budapest International Research and Critics University, 2018)
Field data obtained in five districts / cities in Aceh can be represented as a sample of all regions in Aceh. The cities that are used as primary data references are Kota Lhokseumawe, Banda Aceh, Meulaboh, Takengon, and Langsa City assuming Lhokseumawe and Langsa represent Coastal Aceh, Banda Aceh Aceh Government Center, Meulaboh representing the south west Aceh region and Takengon representing the central Aceh region . It is increasingly clear that Narcotics and Prostitution Practices have become Aceh's problems that must be addressed and overcome by the government and the community in a continuous and simultaneous and comprehensive manner so that they do not become widespread in the future.